Knowledge on hydroxychloroquine prescription and attitude toward its use in COVID-19 – A survey-based study among doctors - T P Afra; N A Uvais; Anuradha Bishnoi; Edavalath Sukesh; Salin Eliyas; N A Bishurul Hafi; T Muhammed Razmi (Indian Journal of Rheumatology)
Background: The use of hydroxychloroquine (HCQ) in COVID-19 had garnered enormous media attention. There were conflicting reports as well as unscientific opinion pieces in the scientific literature also. This study was planned to assess the knowledge, attitude, and practice of health-care professionals regarding HCQ. Methods: An online survey was created with 8 knowledge-based questions (n = 2 fact-based [each scoring 1], n = 6 guideline-based [each scoring 2]), and 6 attitude-based questions, and distribution among a target population of doctors was done using Google™ forms. Results: Of 115 respondents, the majority considered HCQ a safe drug (86.1%) and were in favor of its usage in COVID-19 trials (81.7%) or health-care/contact prophylaxis (60.9%) but against its use as a mass prophylactic agent (80.9%). Contrary to the published guidelines/recommendations, 80% and 55.7% of respondents opined for routine cardiac and glucose-6-phosphate dehydrogenase evaluations before prescribing HCQ. Those who were dealing with COVID-19 patients directly (n = 41) had significantly lower knowledge score compared to the others (6.37 vs. 7.72, P = 0.007). They had significantly lesser awareness for the baseline tests recommended (97.6% vs. 77.0%, P = 0.003). A significantly higher number of these physicians opposed the use of HCQ in clinical trials (26.82% vs. 8.1%, P = 0.027) and health-care/contact prophylaxis (41.5% vs. 16.2%, P = 0.008). Conclusion: Sparse and speedily gathered information on HCQ can influence the practicing doctors, especially those involved directly in COVID-19 patient care, but less familiar with the prescription of this time-tested drug. Possibly, this has a bearing on the counseling of the patients requiring HCQ for non-COVID-19 indications and formulation of new guidelines.